2011
DOI: 10.3171/2011.2.focus10312
|View full text |Cite
|
Sign up to set email alerts
|

Emerging technology in intracranial neuroendoscopy: application of the NICO Myriad

Abstract: Improvement in fiber optics and imaging paved the way for tremendous advancements in neuroendoscopy. These advancements have led to increasingly widespread use of the endoscope in neurosurgical procedures, which in turn incited a technological revolution leading to new approaches, instruments, techniques, and a diverse armamentarium for the treatment of a variety of neurosurgical disorders. Soft-tissue removal is often a rate-limiting aspect to endoscopic procedures, especially when the soft tissue is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 44 publications
0
28
0
1
Order By: Relevance
“…With angled endoscopes, an angled line of sight can be achieved that brings into view previously hidden regions and areas typically blocked by the standard microscope. 18,19 …”
Section: Advances In Neuroendoscopymentioning
confidence: 99%
See 1 more Smart Citation
“…With angled endoscopes, an angled line of sight can be achieved that brings into view previously hidden regions and areas typically blocked by the standard microscope. 18,19 …”
Section: Advances In Neuroendoscopymentioning
confidence: 99%
“…19 In 2005, Kassam et al published the first report of an EEA being used to perform an odontoidectomy. 47 More recently, others have demonstrated the effectiveness of the EEA for the resection of ventral CVJ pathology in case reports and small case series.…”
mentioning
confidence: 99%
“…But the Myriad's optimal usefulness is in minimally invasive approaches and endoscopic tumor removals. Dlouhy et al [1] have reported the utility of the Myriad in the endoscopic removal of brain tumors, primarily pituitary adenomas, colloid cysts and craniopharyngiomas, in 14 adult patients. Garcia-Navarro et al [2] used the Myriad in the endoscopic, endonasal, resections of 13 skull base tumors, primarily macroadenomas.…”
Section: Discussionmentioning
confidence: 98%
“…To date, only one case report and two smaller series describe its use, mostly in the context of endonasal endoscopic surgery. 24,25,26 Our experience with the Myriad NICO has shown it to be a versatile and multifunctional instrument. This instrument was easily maneuvered in conventional skull base approaches (Illustrative case 1) as well as in the keyhole approaches (supraorbital and retrosigmoid), the endonasal endoscopic procedures (Illustrative case 2) and the brain port surgeries (Illustrative case 3).…”
Section: Discussionmentioning
confidence: 99%